2009
DOI: 10.1071/ah090513
|View full text |Cite
|
Sign up to set email alerts
|

Discharge delay in acute care: reasons and determinants of delay in general ward patients

Abstract: To identify the reasons and determinants of discharge delay in acute care patients, information associated with delayed discharge was extracted from the medical record of 1958 patients in a tertiary referral hospital in New South Wales. A logistic regression model was used to examine the association between demographic factors and reasons for discharge delay. Delayed discharge was most commonly associated with the patient's medical conditions, delayed health care or medical consultation, delayed diagnostic ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 15 publications
1
32
0
1
Order By: Relevance
“…, in their Danish population study, also found people who were bereaved of their spouse due to cancer were at greater risk of general or psychiatric hospitalisation in the year post bereavement than non-bereaved matched controls. That people who are bereaved of their spouse remain in hospital longer than non bereaved counterparts, as our study shows, may indicate difficulties associated with complex health and social care needs and living alone (Ou et al, 2009). …”
Section: Discussionmentioning
confidence: 97%
“…, in their Danish population study, also found people who were bereaved of their spouse due to cancer were at greater risk of general or psychiatric hospitalisation in the year post bereavement than non-bereaved matched controls. That people who are bereaved of their spouse remain in hospital longer than non bereaved counterparts, as our study shows, may indicate difficulties associated with complex health and social care needs and living alone (Ou et al, 2009). …”
Section: Discussionmentioning
confidence: 97%
“…(6,33) Patient transfers to ILTC institutions may be delayed due to limited bed availability and administrative delays in the referral process. It is hoped that, as ILTC bed capacities increase in the foreseeable future, (34) the bed crunch situation in hospitals will be eased.…”
Section: Discussionmentioning
confidence: 99%
“…When bed occupancy rates are reduced, patient flow improves by allowing patient transfer to the wards, which, in turn, frees up EDs, so that patients from the waiting room or ambulance bay can be seen and processed, reducing ED length of stay, ambulance diversion and operating room cancellations [20,46-48]. …”
Section: Hospital and System Factorsmentioning
confidence: 99%
“…The reasons for some patient groups being more affected by access block are multifactorial and complex. Deleterious effects as a result of over-crowding and access block have been found in trauma patients [39], and include: Increased delays in transfer to ICU [46-48]; delays in pain treatment [6,7]; increased numbers of patients who did not wait for treatment [36]; increase in patient adverse events [37]; and increased mortality [38,39]. …”
Section: Potential Solutionsmentioning
confidence: 99%